PENGARUH HARGA DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PADA MARKET PLACE SHOPEE - Marwati Setiawan; Moh Wahib; Amris Amris; Abd Karman (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
The Effect of Price and Promotion on Consumer Purchase Interest at Shopee Marketplace (a Case Study on Students of IAIN Fattahul Muluk Papua) is the result of quantitative research which aims to answer the question about the effect of price and promotion on consumer purchase interest at shopee marketplace among students of IAIN Fattahul Muluk Papua. The research method used was quantitative research. The population in this research were students of IAIN Fattahul Muluk Papua academic year 2016 until 2019. The technique of sample selection was simple random sampling and obtained 89 respondents. The data collection technique used a questionnaire. The data analysis technique used multiple linear regression. Data analysis test used SPSS 16.0 application. The research results show that price partially influences consumer purchase interest at shopee marketplace. This is proven by the value of t count in the amount of 2.940 and significance 0.004. Promotion partially influences consumer purchase interest at shopee marketplace. This is proven by t count value 2.846 and the significance 0.006. While based on the result of the simultaneous test of statistic calculation, it can be concluded that price and promotion simultaneously influence consumer purchase interest at shopee marketplace. This is proven by the value of F count 22.736 and significance value 0.000 and determination coefficient 0.346 which means that consumer purchase interest can be explained by price and promotion variables in the amount of 34,6% while the rest is explained by other variables that were not investigated in this research.